Experimental study of the tack of flax fibers based thermoplastic composite reinforcements - Joannes, Mathieu; Gautier, Karine; Arnold, Gilles; Wang, Peng (Wydawnictwo Politechniki Łódzkiej, 2022)
In this article we tested a flax fibres and polypropylene based composite reinforcement in order to determine its adherence to other surfaces around the melting temperature of polypropylene at 165°C. A rheometer with a thermal chamber is used to do a probe-tack test at a constant temperature. This test consists in three steps, the compaction of the sample between two tabs, the relaxation and the separation of the upper tab from the sample. Tackiness corresponds in the traction force measured during the separation. No tackiness was measured during our first tests although we could observe residue on tab surfaces. Further tests where the temperature is lowered beneath the solidification temperature of polypropylene during the relaxation step will be done. Preliminary results for these tests are promising.
Keywords: composites; thermoplastic; tackiness; kompozyty; termoplastyczność; kleistość